1990
DOI: 10.1121/1.399920
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-water matched-field localization off Panama City, Florida

Abstract: The results of a shallow-water localization experiment, performed 19 miles south of Panama City, Florida in October 1985, are presented. The experiment involved a 450-Hz source placed 2.2 km from a vertical array of 16 hydrophones in ∼33 m of water. The experimental site was essentially range independent with a flat, hard, sandy bottom. Successful passive localization of the source was obtained using a maximum-likelihood matched-field processor. Studies were undertaken to determine the robustness of the locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In all three cases the sidelobe level was very close to that of the source peak. In 1990, Feuillade et al [5] reported a single shallow water localization in very shallow water (33 m) using the Capon maximum likehood processor. In 1993, Jesus [6] reported on successful source localizations for transient signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all three cases the sidelobe level was very close to that of the source peak. In 1990, Feuillade et al [5] reported a single shallow water localization in very shallow water (33 m) using the Capon maximum likehood processor. In 1993, Jesus [6] reported on successful source localizations for transient signals.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called 'matched-field' method simply implies that acoustic field observations are 'matched' in some sense to multiple iterations of a forward model as a function of search parameters. This form of processing has been applied to a variety of estimation problems including source localization, see for example [1][2][3][4][5][6][7], tomography [8], and inversion for ocean and ocean bottom properties [9][10][11][12][13]. In many cases the 'matching' is accomplished via a correlation process often referred to as the linear or Bartlett processor.…”
Section: Introductionmentioning
confidence: 99%
“…Years later, Feuillade et at. [33] reported the results of an MFP experiment with full field replicas in the same Gulf of Mexico region where they localized a source at a range of 2.2 km from a 16 element vertical array in 33 m of water. Both conventional and MVDF processors were used, the latter displaying the great ambiguity of a repetitive sidelobe structure.…”
Section: \07mentioning
confidence: 99%
“…20 世纪 80 年代以来, 在声信号处理中引入传播模型的一种备受关注的技术是匹配场处理, 其最 初主要用于解决声源定位问题 [48,49] . 然而, 匹配场处理对模型误差非常敏感, 存在所谓的 "失配" 问 题 [50,51] , 包括环境、系统和统计失配 3 个方面. 大量研究旨在解决该问题, 例如 Richardson 等在匹 配场处理算法中加入先验信息, 得到声源位置的后验概率密度函数, 用来表示未知声传播参数的不确 定度 [52] .…”
Section: 最优的波束形成算法就是使得输出的信号与干扰加噪声的功率之比达到最大 它可以看作一个空unclassified